Description of The Results of Examination of Fasting Blood Sugar and Total Cholesterol of The Elderly Using a Photometer at The Gamping II Health Center Year 2025 - Azzahro, Hasnah Hafishah; Anwar, Chairil; Aryani, Titin (Jurnal Biologi Tropis, 2026)
Older adults are vulnerable to metabolic disorders due to physiological aging processes that may increase the risk of diabetes mellitus and cardiovascular disease. This study aimed to describe fasting blood glucose and total cholesterol levels among elderly patients at the Gamping II Community Health Center using photometric examination methods. This quantitative descriptive study employed a cross-sectional design involving 103 elderly participants selected through total sampling. Fasting blood glucose and total cholesterol levels were measured using standard enzymatic methods with a photometer. The results showed that most respondents had fasting blood glucose levels in the prediabetes category, while total cholesterol levels were generally within the normal to borderline range. The majority of participants were women and aged 60–69 years. These findings indicate a tendency toward metabolic abnormalities among the elderly and highlight the importance of routine metabolic screening for early detection, prevention, and monitoring of age-related metabolic diseases.